Intramuscular Temperature Changes in the Quadriceps Femoris Muscle After Post-Exercise Cold-Water Immersion (10°C for 10 min): A Systematic Review With Meta-Analysis - Livia Freitag; Ron Clijsen; Ron Clijsen; Ron Clijsen; Ron Clijsen; Carlina Deflorin; Wolfgang Taube; Jan Taeymans; Jan Taeymans; Erich Hohenauer; Erich Hohenauer; Erich Hohenauer; et al. (Frontiers Media S.A., 2021)
Post-exercise cold-water immersion (CWI) is a widely accepted recovery strategy for maintaining physical performance output. However, existing review articles about the effects of CWI commonly pool data from very heterogenous study designs and thus, do rarely differentiate between different muscles, different CWI-protocols (duration, temperature, etc.), different forms of activating the muscles before CWI, and different thickness of the subcutaneous adipose tissue. This systematic review therefore aimed to investigate the effects of one particular post-exercise CWI protocol (10°C for 10 min) on intramuscular temperature changes in the quadriceps femoris muscle while accounting for skinfold thickness. An electronic search was conducted on PubMed, LIVIVO, Cochrane Library, and PEDro databases. Pooled data on intramuscular temperature changes were plotted with respect to intramuscular depth to visualize the influence of skinfold thickness. Spearman's rho (rs) was used to assess a possible linear association between skinfold thickness and intramuscular temperature changes. A meta-analysis was performed to investigate the effect of CWI on pre-post intramuscular temperature for each measurement depth. A total of six articles met the inclusion criteria. Maximum intramuscular temperature reduction was 6.40°C with skinfold thickness of 6.50 mm at a depth of 1 cm, 4.50°C with skinfold thickness of 11.00 mm at a depth of 2 cm, and only 1.61°C with skinfold thickness of 10.79 mm at a depth of 3 cm. However, no significant correlations between skinfold thickness and intramuscular temperature reductions were observed at a depth of 1 cm (rs = 0.0), at 2 cm (rs = −0.8) and at 3 cm (rs = −0.5; all p > 0.05). The CWI protocol resulted in significant temperature reductions in the muscle tissue layers at 1 cm (d = −1.92 [95% CI: −3.01 to −0.83] and 2 cm (d = −1.63 [95% CI: −2.20 to −1.06]) but not at 3 cm (p < 0.05). Skinfold thickness and thus, subcutaneous adipose tissue, seems to influence temperature reductions in the muscle tissue only to a small degree. These findings might be useful for practitioners as they demonstrate different intramuscular temperature reductions after a specific post-exercise CWI protocol (10°C for 10 min) in the quadriceps femoris muscle.